Chlorination-promoted skeletal transformation of IPR C76 discovered via trifluoromethylation under the formation of non-IPR C76(CF3)nFm. Issue 20 (30th April 2018) - Tamm, Nadezhda B.; Brotsman, Victor A.; Markov, Vitaliy Yu.; Kemnitz, Erhard; Troyanov, Sergey I.
Abstract : High-temperature chlorination of IPR D 2 -C76 followed by trifluoromethylation resulted in X-ray structures of non-classical, non-IPR C76 (CF3 )14, C76 (CF3 )14 F2, and C76 (CF3 )16 F6 . Abstract : High-temperature chlorination of an Isolated-Pentagon Rule (IPR) D 2 -C76 fullerene followed by high-temperature trifluoromethylation of non-IPR C76 chlorides with CF3 I unexpectedly resulted in a series of non-IPR C76 (CF3 ) n F m compounds. X-ray diffraction study with the use of synchrotron radiation revealed the mixed CF3 /F structures of non-classical, non-IPR C76 (CF3 )14, C76 (CF3 )14 F2, and C76 (CF3 )16 F6 .